Further advances to the nomenclatural, taxonomic and geographic knowledge of the New World Commelina (Commelinaceae): toward a continental treatment - Hassemer, Gustavo (Phytotaxa, 2019)
I present here nomenclatural, taxonomic and geographic novelties in the New World Commelina (Commelinaceae). More specifically, the known distribution of C. longicaulis is expanded to include the Amazon region, and an updated nomenclatural account of the synonymy of C. erecta, C. obliqua and C. tuberosa is presented. Also, the New World synonymy of the Old World species C. benghalensis and C. diffusa is presented, and the first listing of the accepted Commelina species in the Americas since Charles Baron Clarke’s monograph published in 1881 is given. In total, 12 names are typified, and 24 synonymisations newly proposed.